Innate immunity to malaria—The role of monocytes. Issue 1 (16th December 2019) - Dobbs, Katherine R.; Crabtree, Juliet N.; Dent, Arlene E.
Abstract: Monocytes are innate immune cells essential for host protection against malaria. Upon activation, monocytes function to help reduce parasite burden through phagocytosis, cytokine production, and antigen presentation. However, monocytes have also been implicated in the pathogenesis of severe disease through production of damaging inflammatory cytokines, resulting in systemic inflammation and vascular dysfunction. Understanding the molecular pathways influencing the balance between protection and pathology is critical. In this review, we discuss recent data regarding the role of monocytes in human malaria, including studies of innate sensing of the parasite, immunometabolism, and innate immune training. Knowledge gained from these studies may guide rational development of novel antimalarial therapies and inform vaccine development.